Componential Profile and Amylase Inhibiting Activity of Phenolic Compounds from Calendula officinalis L. Leaves - Daniil N. Olennikov; Nina I. Kashchenko (The Scientific World Journal)
An ethanolic extract and its ethyl acetate-soluble fraction from leaves of Calendula officinalis L. (Asteraceae) were found to show an inhibitory effect on amylase. From the crude extract fractions, one new phenolic acid glucoside, 6′-O-vanilloyl-β-D-glucopyranose, was isolated, together with twenty-four known compounds including five phenolic acid glucosides, five phenylpropanoids, five coumarins, and nine flavonoids. Their structures were elucidated based on chemical and spectral data. The main components, isoquercitrin, isorhamnetin-3-O-β-D-glucopyranoside, 3,5-di-O-caffeoylquinic acid, and quercetin-3-O-(6′′-acetyl)-β-D-glucopyranoside, exhibited potent inhibitory effects on amylase.